Relasi Partai Politik Islam Dengan Agama Dan Kekuasaan - Ahyar Nastainul Haq; Muh Dwi Angkasa Putra Amin; Kurniati (Al-Istinbath : Jurnal Ilmu Hukum dan Hukum Keluarga Islam, 2026)
Islamic political parties play a crucial role in Indonesia's presidential system, channeling the political aspirations of Muslims and acting as actors in the dynamics of national power. However, the relationship between religion, Islamic political parties, and power often faces challenges due to political practices that tend to be pragmatic and oriented towards short-term interests. This study aims to analyze the position of Islamic political parties in Indonesia's presidential system and examine the relationship between religion and power in Islamic political practice. The study employed a qualitative method with a library research approach through analysis of various literature sources, scientific journals, and relevant references. The results indicate that Islamic political parties have not been fully able to substantively implement Islamic values ​​in political practice due to the persistent influence of power interests and temporary political coalitions. Nevertheless, religion still plays a role as an ethical foundation that emphasizes the values ​​of justice, trustworthiness, honesty, and the welfare of the people in the exercise of power. Therefore, strengthening the substantive implementation of Islamic values ​​in political activities is necessary so that Islamic political parties can contribute optimally to realizing a democratic, just, and welfare-oriented system of government. Abstrak Partai politik Islam memiliki peran penting dalam sistem presidensial Indonesia sebagai sarana penyaluran aspirasi politik umat Islam sekaligus aktor dalam dinamika kekuasaan nasional. Namun, hubungan antara agama, partai politik Islam, dan kekuasaan sering menghadapi tantangan akibat praktik politik yang cenderung pragmatis dan berorientasi pada kepentingan jangka pendek. Penelitian ini bertujuan untuk menganalisis posisi partai politik Islam dalam sistem presidensial Indonesia serta mengkaji hubungan agama dan kekuasaan dalam praktik politik Islam. Penelitian menggunakan metode kualitatif dengan pendekatan studi pustaka (library research) melalui analisis berbagai sumber literatur, jurnal ilmiah, dan referensi yang relevan. Hasil penelitian menunjukkan bahwa partai politik Islam belum sepenuhnya mampu mengimplementasikan nilai-nilai Islam secara substantif dalam praktik politik karena masih kuatnya pengaruh kepentingan kekuasaan dan koalisi politik yang bersifat sementara. Meskipun demikian, agama tetap memiliki peran sebagai landasan etis yang menekankan nilai keadilan, amanah, kejujuran, dan kemaslahatan umat dalam penyelenggaraan kekuasaan. Oleh karena itu, diperlukan penguatan implementasi nilai-nilai Islam yang substantif dalam aktivitas politik agar partai politik Islam dapat berkontribusi secara optimal dalam mewujudkan sistem pemerintahan yang demokratis, adil, dan berorientasi pada kesejahteraan masyarakat.